Showstopper - Lovesey, Peter (Lovesey, Peter. Peter Diamond mystery., 2022)
"Since the start of the hit TV show Swift in 2013, its cast and crew have been plagued by misfortune. First, a star actress pulls out of the show before it begins--and by 2019, there have been multiple injuries by fall, fire, or drowning; two deaths; and two missing persons cases. The popular media around Bath, England, quickly decides it's a curse, but is it as simple as that? Is someone behind these fishy incidents? Peter Diamond, Chief Superintendent of the Avon and Somerset Murder Squad, is on the case, and he'll start by looking for the two currently missing men. But while the investigation is underway, the producer of the show goes missing, complicating already complex matters even further. Unfortunately, Peter's boss, Georgina, is pushing retirement on him; he may be forced to retire if he can't solve the case. Will this be the end for Peter Diamond?"--